PERANAN INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) DALAM MENGEMBANGKAN PARIWISATA DANAU TOBA “MONACO OF ASIA” - Arwin Tannuary; Ambo Enre (Jurnal Ekonomi dan Bisnis (EK dan BI), 2021)
Lake Toba is one of the largest caldera lakes in the world, located in North Sumatra Province, Mel176 km to the west of Medan City. Lake Toba, which is one of the super priority tourist destinations that has been certified by UNESCO Global Geopark (UGG) at the world level. This provides a huge opportunity and responsibility for Indonesia, in advancing the economy and sustainable development in the area around Lake Toba. This study discusses the extent of the Role of Information and Communication Technology (ICT) in Developing Lake Toba Tourism as the "Monaco of Asia". So that the use of ICT in the development of Danu Toba tourism will increase the number of local and international tourist visitors in the Lake Toba area. The results obtained in this study indicate that the role of information communication technology has a positive and significant effect on the development of Lake Toba Tourism. This is indicated by the tcount value of 53,961 which is greater than the t-table value of 0.088 and the significance value of 0.000 which is smaller than the 0.05 significance value. So it can be concluded that Ha is accepted. which means, there is a significant positive influence of information communication technology in developing Lake Toba Tourism "Monaco of Asia".